PERANCANGAN PACKAGING USAHA TEMPE APDET JL. DR. M. HATTA KETAPING PADANG - APRILIANI PUTRI, Dra. Zubaidah, M.Sn., Riri Trinanda, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Tempe date of profile update is located at Jl. Dr.M. Ketaping Hatta Padang. This effort is an attempt First Instance in the city of Padang, because this business process food tempe tempeh traditional into modern food. The goal of this effort to entice consumers to gravitate back to traditional foods that are less favored by teenagers.The tempeh effort existence is still unclear, it is the lack of business owners do promosian via social media and fliers. Previous packaging only using ordinary plastic. From the problems of interest to the design is to make tempeh date of profile update product packaging design.The design of packaging is carried out by stages such as data collection and design. This collection process through interviews with business owners. While the data analysis process by means of a SWOT analysis (Strength, Weakness, Opportunity, Thethreat) in getting through the collection of data observation and documentation directly to the business location. Further analysis of a product and designing products. This design will show the final design at the date of profile update tempeh products. This packaging design adjusted to the date of profile update tempe own business.Keywords: Packaging, Tempe date of profile update, design.